LEGAL ANALYSIS OF NICKEL MINING EXPANSION IN RAJA AMPAT FROM THE PERSPECTIVE OF RENEWABLE ENERGY DEVELOPMENT AND ENVIRONMENTAL SUSTAINABILITY PRINCIPLES - dianisadiawati; Cahya Utami Aldana; Ainun Nabilah (Journal of Governance and Law Reform, 2026)
This study aims to examine the expansion of nickel mining in Raja Ampat within the framework of natural resource law, particularly regarding its role as a supplier of essential minerals for national renewable energy development. Using normative juridical methods, this study examines various regulations regarding environmental sustainability, licensing, and the application of the precautionary principle as a benchmark for protecting conservation areas and the rights of indigenous peoples. The analysis results indicate a policy misalignment between the green energy transition agenda at the national level and the principle of ecological protection in conservation areas. Regulatory gaps are evident in the weak enforcement of environmental standards, the suboptimal synchronization of mining permits in marine conservation areas, and the failure to fulfill the Free, Prior and Informed Consent (FPIC) mechanism for affected indigenous communities. These conditions reflect that green energy development still has the potential to cause ecological and social injustice, especially in vulnerable areas such as Raja Ampat. This study concludes that strengthening regulations and harmonizing policies is urgently needed, including ensuring compliance with the precautionary principle, biodiversity protection, and upholding the rights of indigenous peoples at every stage of mining licensing and operations. Without environmentally just policy reforms, the Raja Ampat conservation area risks becoming a “sacrifice zone” in the national green energy transition project.